1995
DOI: 10.1111/j.1472-765x.1995.tb01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between Penner serotyping and polymerase chain reaction fingerprinting of Campylobacter isolated from poultry and other animal sources

Abstract: Thirty-four Campylobacter jejuni or coli strains, isolated from various livestock and darkling beetles from two Dutch poultry farms during different broiler production cycles, were subjected to Penner serotyping and polymerase chain reaction (PCR) fingerprint analysis. Ten different Penner serotypes were determined in the isolates. Visual scoring of the PCR fingerprints resulted in 14 clearly different profiles. Some strains with identical Penner serotypes exhibited different PCR fingerprints and conversely st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…C. jejuni serotype HS1, HS2, and HS4 isolates exhibited considerable genetic diversity within the serogroups as determined by both PFGE (28,73) and fla typing (9, 68) and, to a lesser extent, by ribotyping and RAPD analysis (20,28,40,73). A comparison of RAPD fingerprinting and HS antigen serotyping results suggested that sometimes there can be correlations between the data obtained with these two typing schemes (55); however, such correlations are unpredictable (1,36).…”
Section: Comparison Of Genotypic and Phenotypic Subtyping Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. jejuni serotype HS1, HS2, and HS4 isolates exhibited considerable genetic diversity within the serogroups as determined by both PFGE (28,73) and fla typing (9, 68) and, to a lesser extent, by ribotyping and RAPD analysis (20,28,40,73). A comparison of RAPD fingerprinting and HS antigen serotyping results suggested that sometimes there can be correlations between the data obtained with these two typing schemes (55); however, such correlations are unpredictable (1,36).…”
Section: Comparison Of Genotypic and Phenotypic Subtyping Methodsmentioning
confidence: 99%
“…This approach has been used to determine the genotypic subtypes of C. jejuni and C. upsaliensis (30), since these species do not contain repetitive sequences which can be used for high-fidelity ERIC amplification. Combinations of an ERIC primer and a randomly chosen primer have also been used (1,17,30,38). However, the reproducibility of the results obtained with the combined RAPD-ERIC amplification technique is still low.…”
Section: Rapd Analysismentioning
confidence: 99%
“…In terms of invertebrates carrying this pathogen, pathogenic serotypes of E. coli have been isolated from the darkling beetle in both adult and larva forms and from the lesser mealworm (Alphitobus diaperinus) in poultry farms where Salmonella and Campylobacter spp. were also present (1,14,18). Laboratory experiments have further confirmed lesser mealworms as potential vectors of E. coli, Salmonella, and Campylobacter (27,46).…”
mentioning
confidence: 80%
“…Poultry, hosting very frequently C. jejuni, are considered as one of the main sources of the agent. A great number of papers (Aarts et al 1995;Annan-Prah et al 1988;Jacobs-Reitsma et al 1995) were engaged in studying and comparing serotypes isolated from patients and poultry. Serotypes from poultry only partly agree with isolates from human patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of serotyping methods is limited, and, therefore, methods of genotyping have been employed more and more recently. It is possible to combine phenotypic methods and genotypic identification using molecular methods which may reliably identify strains isolated from animals and human patients, their characteristics and probable routes of transmission (Aarts et al 1995;Madden et al 1998).…”
mentioning
confidence: 99%